Synthesis and gastroprotective activities of some zinc (II) complexes derived from (E)-2-(1-(2-(piperazin-1-yl)ethylimino)ethyl)phenol and (E)-4-(1-(2-(piperazin-1-yl)ethylimino)ethyl)benzene-1,3-diol Schiff bases against aspirin induced ulceration - Salga, M.S.; Ali, Hapipah Mohd; Abdulla, Mahmood Ameen; Abdelwahab, S.I.; ElhassanTaha, M.M.; Yagoub, U. (Elsevier, 2017)
This study describes the protective effects of piperazine derived compounds against aspirin induced gastric injuries and evaluated the role of nitric oxide, inflammatory cytokines and serum level of aspartate aminotransaminases (AST), alanine aminotransaminases (ALT), high density lipoprotein (HDL) and malondialdehyde (MDA). The oral administration of the compounds at doses 30 and 60 mg/kg protected the gastric against the nectrotizing effects of aspirin. The level of nitric oxide (NO) was elevated in the group pretreated with the compounds. The results also showed that pre-treatment with piperazine compounds has led to the decrease in the amount of MDA and increased the activity of AST, ALT and HDL. In conclusion, pre-treatment with piperazine derived compounds; (E)-2-(1-(2-(piperazin-1-yl)ethylimino)ethyl)phenol (2HP), (E)-4-(1-(2-(piperazin-1-yl)ethylimino)ethyl) benzene-1,3-diol (DHP) and their zinc complexes has provided a significant protection to the gastric from damaging effects of aspirin.